Settling on the Temporary - Melikoğlu Eke, Armağan Seçil; USTA, GÜLAY (My University, 2019)
Several thoughts on temporality - a term for things lasting or used for only a short period of time as opposed to the permanent, or for things that are palliative- have been produced and these thoughts appear in various studies. On the other hand, “place” is at the center of architectural discussions and researches. The concept of “temporality” has recently been popular among the theories and practices of the discipline of architecture. Although establishing “the first shelter to be protected against environmental conditions" -as one of the fundamental reasons of the emergence of architecture- is a representation of temporality, permanence became the core of humans’ act of forming shelters. However today, people are migrating and leaving their homes. Migration is an act changing places, either voluntarily or compulsorily, due to economics, war, natural disasters. People who leave the places they once inhabited are given new temporary models of shelter such as refugee camps or disaster relief housing. Things become clearer when one looks at the number of people who had to change places due to ongoing wars. For instance, 6.864.445 citizens of Syria moved out of their country in 2017 and %37,57 of the remaining population had to change places (URL-1). A great number of people who migrated from Syria because of the civil war settled in Turkey, Jordan, Lebanon, Saudi Arabia and Iraq. According to the data of International Organization for Migration (IOM), the immigrant population in Turkey constituted % 3,77 of the settled population in 2015 but this percentage changed to % 6,03 in 2017. The number of immigrant moving from Syria to Turkey was 1.568.494 in 2015, however, this number raised to 4.880.917 in 2017 (URL-1). The total number of immigrants in Turkey is now recorded as 4.880.917 (URL-1). This data explains that new approaches and solutions on the subjects of homelands, homelessness, migration, refugees, asylum seekers should be proposed and developed because “homelessness" means losing home, language, culture, friends, relatives, in other words, it is being deprived of daily routine. What is more, the immigrants get into contact with a society which they are unfamiliar with and they seek refuge in that society. Therefore, spaces that are arranged for people away from their homelands, namely immigrants, should give them the opportunity to re-establish their routine and form relations with the new society they live in people. On the one hand, there is the fact of being migrant, change of places, temporality and on the other hand, there are concepts representing permanency like settlement, identification, adaptation, and home. New places are being established for those who are trying to survive among such concepts. Heidegger establishes his philosophy of place on “dasein” - the ways in which humans are and exit in the world- and on “dwelling", as in residing somewhere. Consequently, he claims that places represent a form of taking root for the being and experience of the human and that they are not just dead locations as they possess qualities related to life. According to the architectural design approach which is based on Martin Heidegger’s “Building Dwelling Thinking”, dwelling is one’s seamlessly identification with the environment offering integrity. It is natural way of human existence. It is suggested that human beings are not just amphibian forms of consciousness. Instead, they are in need of belonging to a ‘place’ that has distinct features. This approach defines place through a hypothetical case of a bridge and suggests that the place creates the dwelling though the bridge (URL-2). It could be observed that one of the very recent issues that architecture deals with in the context of temporality is the need for designing places which would meet social and humane needs. Producing spaces that can be called as “place” by people who change places because of migration has become a subject for which a considerable number of designers are looking for new and creative solutions. For instance, Shigeru Ban is known for his work with recycled cardboard tubes built in areas where disasters took place. Alejandro Aravena won the Pritzker Architecture Prize thanks to his participatory housing projects. Projects which have been realized so far show that fast and easily built modular systems, productions carried out with already made tools, conversion of desolated urban spaces, using alternative places for settlement and creating the sense of belonging by user participation have been examples of various approaches. Under the light of abovementioned information, this paper aims to investigate the approaches towards designs of temporary/permanent places for people who change places. Applied examples are analyzed and evaluated within the scope of this study. The findings gained through the analysis and evaluation are considered to be as possible data which can be used for designing temporary/permanent places in Turkey.
Keywords: Temporality; Migration; Place; Placeness; Belonging